2020
DOI: 10.1016/j.bbrc.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-mediated H3K27me3 inhibits ACE2 expression

Abstract: Available online xxx Keywords: Coronavirus SARS-CoV-2 ACE2 EZH2 H3.3 a b s t r a c tThe outbreak of corona virus disease 2019 (COVID-19) caused by SARS-CoV-2 infection is spreading globally and quickly, leading to emerging health issues. SARS-CoV-2 enters into and infects host cells through its spike glycoprotein recognizing the cell receptor Angiotensin-converting enzyme II (ACE2).Here, we noticed that ACE2 was further enhanced by SARS-CoV-2 infection. Human germ cells and early embryos express high level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 30 publications
4
52
0
Order By: Relevance
“…In agreement with the inverse correlation between ACE2 level and H3K27me3, ACE2 expression in human ESCs was upregulated following EZH2 knock-out (Li Y. et al, 2020). On the other side, recovery of EZH2 restored basal ACE2 levels.…”
Section: Transcriptional Post-transcriptional and Post-translationasupporting
confidence: 77%
See 3 more Smart Citations
“…In agreement with the inverse correlation between ACE2 level and H3K27me3, ACE2 expression in human ESCs was upregulated following EZH2 knock-out (Li Y. et al, 2020). On the other side, recovery of EZH2 restored basal ACE2 levels.…”
Section: Transcriptional Post-transcriptional and Post-translationasupporting
confidence: 77%
“…On the other side, recovery of EZH2 restored basal ACE2 levels. Chromatin immunoprecipitation sequencing (ChIP-seq) showed that EZH2 depletion induced H3K27me3 decrease, with concomitant H3K27ac increase, at ACE2 promoter in human ESCs (Li Y. et al, 2020). The role of H3 methylation and acetylation in the epigenetic regulation of ACE2 was also hypothesized by Pinto et al, who demonstrated that co-morbidities such as hypertension, diabetes, and chronic obstructive lung disease increase ACE2 transcription in the lung (Pinto et al, 2020).…”
Section: Transcriptional Post-transcriptional and Post-translationamentioning
confidence: 91%
See 2 more Smart Citations
“…Given that SARS-CoV-2 utilizes structures such as lipid rafts to mediate its entry process, the authors recommend exploring the possibilities of employing substances like cyclodextrin and sterols to interfere with such viral attachment and entry-enabling mechanisms. Along similar lines of conjecturing prospective therapeutic candidates, EZH2-mediated H3K27me3 at ACE2 promoter regions has been demonstrated to inhibit the expression of ACE2 receptors in mammalian cell lines, as indicated by data from RNA-Seq and CHIP-Seq experiments (Li et al 2020d ).…”
Section: Treatment Strategies For Sars-cov-2 Infectionsmentioning
confidence: 93%